Environmental Information System: Conceptual Framework of Supply Chain Process - Nurul Fadly Habidin; Sharul Effendy Janudin; Norlaile Salleh Hudin; Mohd Nazir Md Zabit; Nursyazwani Mohd Fuzi; Sharon Yong Yee Ong (International Journal of Supply Chain Management, 2019)
The purpose of this study is to review the conceptual framework for supply chain process of EIS. Two supply chain process of EIS (technology and processes) had been identified. This study used IBM Statistical Package for Social Sciences (SPSS) Statistics and analysed the data by using SPSS and Structural Equation Modelling (SEM) technique. For practical implications, this research provides important guidelines for manufacturer and related companies to implement the supply chain process of EIS in order to improve the supply chain and information system. Therefore, the identification of EIS is significant to the Malaysian manufacturing industry in order to improve the supply chain process.